Hierarchical Manipulation of Block Copolymer Patterns on 3D Topographic Substrates: Beyond Graphoepitaxy. Issue 32 (6th June 2016) - Park, Sungjune; Cheng, Xiao; Böker, Alexander; Tsarkova, Larisa
Abstract : Templates of complex nanopatterns in a form of hierarchically sequenced dots and stripes can be generated in block copolymer films on lithography‐free 3D topographic substrates. The approach exploits thickness‐ and swelling‐responsive morphological behavior of block copolymers, and demonstrates novel possibilities of topography‐guided registration of nanopatterns due to periodic confinement and spontaneous orthogonal flow‐fields.